Coating cutting tool and preparation method thereof

By adopting a multi-layer coating structure on the cutting tool, including MTCVD TiCN coating with high texture coefficient and Al2O3 coating, the hardness, wear resistance and cutting of steel, cast iron and stainless steel materials in the prior art are solved. The problem of insufficient impact resistance achieves both high performance and stability.

CN119433494APending Publication Date: 2025-02-14ZHUZHOU CEMENTED CARBIDE CUTTING TOOLS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310973792.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-03
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art is difficult to achieve both high hardness, wear resistance, impact resistance and quality stability in the cutting processing of steel, cast iron and stainless steel materials.

Method used

A multi-layer coating structure is adopted, including at least one MTCVD TiCN coating with a columnar crystal structure, the (220) crystal surface of the coating is preferably textured, texture coefficient Tc(220)≥3, and the grain size is 0.1 μm to 0.4 μm, and a hard base layer, an intermediate layer and an Al2O3 coating were deposited in sequence on the tool substrate.

Benefits of technology

The hardness, wear resistance, impact resistance and peeling resistance of the coating cutting tool are improved, while ensuring the quality stability of the tool.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433494A_ABST
    Figure CN119433494A_ABST
Patent Text Reader

Abstract

The invention discloses a coated cutting tool and a preparation method thereof.The coated cutting tool comprises a tool base body and a multi-layer coating covering the surface of the tool base body, the multi-layer coating at least comprises a layer of MTCVD TiCN coating of a columnar crystal structure, the MTCVD TiCN coating has (220) crystal face preferred texture orientation, the texture coefficient Tc (220) is larger than or equal to 3, the diffraction angle 2 theta of the (220) crystal face ranges from 60.75 degrees to 61.05 degrees, and the thickness of the MTCVD TiCN coating ranges from 20 micrometers to 30 micrometers. The grain size of the MTCVD TiCN coating ranges from 0.1 micrometer to 0.4 micrometer. The preparation method comprises the steps of preparing the cutter base body and the multiple coatings. The coating cutting tool has the advantages of high hardness, high wear resistance, high impact resistance, stripping resistance and the like, and the product quality stability is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of coating cutting tool preparation, and relates to a coating cutting tool and a preparation method thereof, and specifically relates to a CVD coating cutting tool for metal cutting processing and a preparation method thereof. Background Art

[0002] Chip forming machining of steel, cast iron, high temperature alloys and other materials usually uses cutting tools made of cemented carbide, cermet, cubic boron carbide, high speed steel and other materials, while wear-resistant coatings such as TiN, TiCN, TiAlN, Al2O3 are used to improve the wear resistance and tool life of the tool. CVD is widely used in tool preparation because it can achieve large-scale deposition of coating materials such as TiN, TiCN, Al2O3, and can complete surface coating of complex geometric structures.

[0003] The multilayer composite coating composed of the MTCVD TiCN coating with columnar crystal structure and the α-Al2O3 coating prepared by the medium temperature chemical vapor deposition (MT CVD) technology is a typical coating used in the tool field. In view of the diversity of cutting materials, the diversity of cutting methods, and the trend of efficient and intelligent cutting, the composition and microstructure of each coating in the multilayer composite coating can be regulated and optimized to further improve the performance of the tool and meet higher requirements of cutting.

[0004] Larsson (Microstructure and properties of Ti(C,N) coatings produced by moderate temperature chemical vapour deposition. Thin Sold Film 402 (2002) 203-210) disclosed the use of MTCVD technology to prepare MTCVDTiCN coatings on cemented carbide surfaces with relatively large Tc(422), a grain size of about 0.5 μm, and an atomic ratio of carbon to carbon and nitrogen C / (C+N) of about 0.6. Compared with TiCN coated tools prepared by high temperature chemical vapor deposition (HTCVD) technology, MTCVD TiCN coated tools have better edge strength due to the absence of brittle η phase, but insufficient wear resistance.

[0005] CN101138900B discloses a (422) oriented columnar structure TiCN coating, which increases the C content in the TiCN coating by adding chain hydrocarbons with 2 to 20 carbon atoms in the reaction atmosphere, and the atomic ratio C / (C+N) of carbon to the sum of carbon and nitrogen is in the range of 0.7 to 0.9, and the average grain size is 0.05 to 0.5 μm. The coating hardness is increased and the wear resistance is improved, but the strength is insufficient and the stability is low.

[0006] CN104053815A discloses a (422) oriented TiCN coating, with a C / (C+N) range of 0.5 to 0.65 and an average grain size of 0.05 to 0.4 μm. Tc(422)+TC(311)>5.5. Compared with conventional MTCVD TiCN, the coating has a smooth surface and achieves a smooth effect. The thickness is controlled at 5 to 15 μm, and is used to improve the performance of ductile iron turning and high-speed turning, but the wear resistance is insufficient.

[0007] CN105308210B discloses a fine-grained TiCN coating with a C / (C+N) range of 0.5 to 0.65 and an average grain size of 0.05 to 0.2 μm. Tc(422)+TC(311)≤5.5. Compared with conventional MTCVD TiCN, it has a smooth surface, achieves a smoothing effect, improves heat crack resistance and spalling resistance during milling, and has a thickness of 2 to 7 μm. It is used for milling of gray iron and ductile iron. However, the grains are too fine, resulting in a decrease in tool strength.

[0008] In recent years, machining conditions have improved in the field of mechanical machining, and automation has been widely used, requiring highly stable and wear-resistant cutting tools. Summary of the invention

[0009] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a coated cutting tool having excellent hardness, wear resistance, impact resistance, anti-flaking performance, and high quality stability, and a preparation method thereof. The CVD coated tool takes into account the optimization of microstructure and performance, and achieves excellent cutting performance in the general cutting of steel, cast iron and stainless steel materials.

[0010] In order to solve the above technical problems, the present invention adopts the following technical solutions.

[0011] A coated cutting tool comprises a tool substrate and a multilayer coating covered on the surface of the tool substrate, wherein the multilayer coating comprises at least one layer of MTCVD TiCN coating having a columnar crystal structure, the MTCVD TiCN coating having a (220) crystal plane preferential texture orientation, a texture coefficient Tc(220)≥3, and a diffraction angle 2θ of the (220) crystal plane in the range of 60.75° to 61.05° (in an X-ray diffraction analysis using CuKa radiation); the grain size of the MTCVD TiCN coating is 0.1μm to 0.4μm.

[0012] For the above-mentioned coated cutting tool, preferably, the Tc(220) of the MTCVD TiCN coating is ≥4.

[0013] For the above-mentioned coated cutting tool, preferably, the Tc(220) of the MTCVD TiCN coating is ≥5.

[0014] For the above-mentioned coated cutting tool, preferably, the MTCVD TiCN coating has a diffraction angle 2θ of the (220) crystal plane of 60.85° to 60.95° in an X-ray diffraction analysis using CuKa radiation.

[0015] For the above-mentioned coated cutting tool, preferably, the grain size of the MTCVD TiCN coating is 0.15 μm to 0.3 μm.

[0016] For the above-mentioned coated cutting tool, preferably, the thickness of the MTCVD TiCN coating is 5 μm to 20 μm.

[0017] For the above-mentioned coated cutting tool, more preferably, the thickness of the MTCVD TiCN coating is 7 μm to 15 μm.

[0018] Preferably, the coated cutting tool described above further has a hard base layer between the MTCVD TiCN coating and the tool substrate, the hard base layer comprising at least one of a TiN layer, a TiCN layer and a TiC layer, and the thickness of the hard base layer is 0.1 μm to 1.0 μm.

[0019] For the above-mentioned coated cutting tool, preferably, the surface of the MTCVD TiCN coating is provided with an Al2O3 coating, and the thickness of the Al2O3 coating is 2 μm to 15 μm.

[0020] For the above-mentioned coated cutting tool, preferably, the thickness of the Al2O3 coating is 3 μm to 10 μm; and the Al2O3 coating is an α-Al2O3 coating or a k-Al2O3 coating.

[0021] For the above-mentioned coated cutting tool, preferably, the thickness of the Al2O3 coating is 4 μm to 7 μm.

[0022] For the above-mentioned coated cutting tool, preferably, an intermediate layer is provided between the MTCVD TiCN coating and the Al2O3 coating, and the intermediate layer is composed of two or more layers of a TiN layer, a TiCN layer, a TiCNO layer, a TiAlCNO layer and a TiCO layer, and the outermost layer of the intermediate layer is one of a TiCNO layer, a TiAlCNO layer and a TiCO layer, and the thickness of the intermediate layer is 0.3μm to 1.0μm.

[0023] For the above-mentioned coated cutting tool, preferably, the surface of the Al2O3 coating is provided with a color layer, the color layer comprises a combination of one or more of a TiN layer, a ZrN layer, a TiC layer and a TiB layer, and the thickness of the color layer is 0.2μm to 2.0μm.

[0024] As a general technical concept, the present invention also provides a method for preparing the above-mentioned coated cutting tool, comprising the following steps:

[0025] (1) Prepare the tool base;

[0026] (2) A TiCN coating is deposited by an MTCVD process to obtain an MTCVD TiCN coating, wherein the process conditions include: a deposition temperature of 870°C to 950°C, a pressure of 40 mbar to 100 mbar, TiCl4-CH3CN-HCl-N2-H2 as a deposition atmosphere system, a reaction gas comprising 10.0 mol% to 50.0 mol% N2, 1.0 mol% to 4.0 mol% TiCl4, 0.2 mol% to 1 mol% CH3CN, 0 to 5 mol% HCl, and the remainder being H2 gas, wherein the molar ratio of TiCl4 to CH3CN is 4 to 7:1.

[0027] The method for preparing the above-mentioned coated cutting tool preferably further includes a step of depositing a hard base layer between step (1) and step (2): depositing the hard base layer on the tool substrate using a CVD process, and then depositing an MTCVD TiCN coating on the hard base layer; the hard base layer includes at least one of a TiN layer, a TiCN layer and a TiC layer, and the thickness of the hard base layer is 0.1 μm to 1.0 μm.

[0028] The method for preparing the above-mentioned coated cutting tool preferably further includes the step of depositing an intermediate layer after step (2): depositing the intermediate layer on the MTCVD TiCN coating using a CVD process; the intermediate layer includes a combination of one or more layers of a TiN layer, a TiCN layer, a TiCNO layer, a TiAlCNO layer and a TiCO layer, and the thickness of the intermediate layer is 0.3μm to 1.0μm.

[0029] The method for preparing the coated cutting tool mentioned above preferably further comprises the step of depositing an Al2O3 coating after depositing the intermediate layer: depositing the Al2O3 coating on the intermediate layer using a CVD process; the thickness of the Al2O3 coating is 2 μm to 15 μm.

[0030] The preparation method of the above-mentioned coated cutting tool preferably further includes the step of depositing a color layer after depositing the Al2O3 coating: depositing the color layer on the Al2O3 coating using a CVD process; the color layer includes a combination of one or more layers of a TiN layer, a ZrN layer, a TiC layer and a TiB layer, and the thickness of the color layer is 0.2μm to 2.0μm.

[0031] The above-mentioned method for preparing the coated cutting tool, the multi-layer preparation specifically comprises the following steps:

[0032] (1) preparing a tool substrate;

[0033] (2) depositing a hard base layer on the tool substrate using a CVD process;

[0034] (3) depositing a TiCN coating on the hard substrate layer using an MTCVD process to obtain an MTCVD TiCN coating, wherein the process conditions include: a deposition temperature of 870°C to 950°C, a pressure of 40 mbar to 100 mbar, TiCl4-CH3CN-HCl-N2-H2 as a deposition atmosphere system, a reaction gas comprising 10.0 mol% to 50.0 mol% of N2, 1.0 mol% to 4.0 mol% of TiCl4, 0.2 mol% to 1 mol% of CH3CN, 0 to 5 mol% of HCl, and the remainder being H2 gas, wherein the molar ratio of TiCl4 to CH3CN is 4 to 7:1;

[0035] (4) depositing at least one of a TiCNO layer and a TiAlCNO layer as an intermediate layer on the MTCVD TiCN coating by a CVD process;

[0036] (5) depositing an Al2O3 coating on the intermediate layer using a CVD process;

[0037] (6) Depositing a color layer on the Al2O3 coating using a CVD process.

[0038] In the present invention, the texture coefficient Tc(hkl) of the MTCVD TiCN coating is defined as follows:

[0039]

[0040] Where I(hkl) is the measured intensity of the (hkl) crystal plane diffraction peak, I0(hkl) is the intensity of the standard powder diffraction peak according to ICDD PDF card number 42-1489, n is the number of crystal plane diffraction used in the calculation, and the (hkl) crystal plane diffraction peaks used are (111)(200)(220)(311)(331)(420)(422)(511). The maximum value of Tc(hkl) does not exceed 8.

[0041] In the present invention, the texture coefficient of the MTCVD TiCN coating is Tc(220)≥3, preferably TC(220)≥4, and more preferably Tc(220)≥5.

[0042] The inventors found that by controlling the MTCVD TiCN deposition conditions, Tc(220) was increased, and the increase in Tc(220) was beneficial to increasing the hardness of the MTCVD TiCN coating and the wear resistance of the tool.

[0043] In the present invention, the grain size of the MTCVD TiCN coating is 0.1 μm to 0.4 μm, preferably 0.15 to 0.3 μm. If the coating grains are too fine, it is easy to break, and if the coating grains are too coarse, the wear resistance is insufficient.

[0044] In the present invention, in the X-ray diffraction pattern obtained by X-ray diffraction analysis of the MTCVD TiCN coating, the diffraction angle 2θ of the (220) crystal plane is between 60.75° and 61.05°, and the position of the diffraction angle is related to the atomic ratio C / (C+N) of carbon to the sum of carbon and nitrogen in the coating. The higher the C / (C+N) in the coating, the lower the diffraction angle 2θ value of the (220) crystal plane. The instrumental offset of the diffraction angle 2θ of the (220) crystal plane of the MTCVD TiCN coating is corrected by the offset Δ2θ of the diffraction angle 2θ of the WC (110) crystal plane in the substrate. The offset Δ2θ is defined as:

[0045] Δ2θ=2θWC(110)-2θ0WC(110)

[0046] 2θTiCN(220)=2θ0TiCN(220)+Δ2θ

[0047] 2θWC(110) is the measurement position of the diffraction angle 2θ of the WC(110) crystal plane in the matrix X-ray diffraction pattern.

[0048] 2θ0WC(110) is the diffraction angle 2θ position of the WC(110) crystal plane according to PDF card No. 25-1047 of ICDD.

[0049] 2θTiCN(220) is the measurement position of the diffraction angle 2θ of the (220) crystal plane in the X-ray diffraction pattern of the TiCN coating.

[0050] 2θ0TiCN(220) is the diffraction angle 2θ position of the TiCN(220) crystal plane according to PDF card No. 42-1489 of ICDD.

[0051] In the present invention, the thickness of the MTCVD TiCN coating is 5 to 20 μm. Increasing the coating thickness can improve the wear resistance of the tool.

[0052] In the present invention, other coatings, such as Al2O3 coating, TiN, etc., are coated on the surface of the MTCVD TiCN coating. The Al2O3 coating can improve the resistance to oxidation wear and improve the performance of the tool in high-temperature working conditions such as high-speed machining. The color layer can improve the tool usage identification function.

[0053] In the present invention, there is an intermediate layer between the MTCVD TiCN coating and the Al2O3 coating, and the intermediate layer comprises a combination of one or more layers of a TiN layer, a TiCN layer, a TiCNO layer, a TiAlCNO layer and a TiCO layer. The intermediate layer can improve the bonding strength of the outer Al2O3 coating and prevent peeling.

[0054] In the present invention, a hard base layer, an MTCVD TiCN layer, an intermediate layer, and an Al2O3 layer are sequentially deposited on the surface of the substrate. The thickness of the hard base layer is 0.1-1.0 μm, and the thickness of the MTCVD TiCN layer is 5-20 μm, preferably 7-15 μm. The thickness of the intermediate layer is 0.3-1.0 μm, and the thickness of the Al2O3 layer is 2-15 μm, preferably 3-10 μm, and more preferably 4-7 μm. The Al2O3 layer can be a k-Al2O3 layer or an a-Al2O3 layer. The intermediate layer includes a TiCO layer, and a HTCVD TiCN layer can be selectively deposited between the MTCVD TiCN layer and the TiCO layer, and the thickness of the HTCVD TiCN layer is 0.2-0.5 μm. A color layer can be selectively deposited on the surface of the Al2O3 layer, and the color layer can be selected from one or more combinations of TiN layer, ZrN layer, TiC layer, and TiB layer, and the thickness of the color layer is 0.2-2.0 μm.

[0055] In the present invention, the tool matrix is ​​mainly composed of cemented carbide, metal ceramics, ceramics or superhard materials (superhard materials such as cubic boron nitride, polycrystalline diamond, etc.).

[0056] Compared with the prior art, the advantages of the present invention are mainly:

[0057] (1) The coated cutting tool of the present invention comprises an MTCVD TiCN coating, which has a high texture coefficient of preferred orientation, Tc(220)≥3 (more preferably ≥5), the coating hardness is improved, and the wear resistance of the tool is increased. The MTCVD TiCN coating has fine grains, a smooth deposition surface, and a grain size of 0.1μm to 0.4μm (preferably 0.15μm to 0.3μm). If the coating grains are too fine, they are prone to breakage, and if the coating grains are too coarse, the wear resistance is insufficient. The coated cutting tool of the present invention also has the advantages of high hardness, good wear resistance, fine grains, smooth surface, high strength, and good stability.

[0058] (2) The preparation process of the present invention has high coating deposition efficiency and good deposition uniformity, and at the same time obtains a coating with extremely high surface smoothness, and the product quality is highly stable, and the hardness, wear resistance and strength are excellent. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 This is the X-ray diffraction spectrum of sample 1 in Example 1 of the present invention.

[0060] Figure 2 This is the X-ray diffraction spectrum of sample 2 in Example 2 of the present invention.

[0061] Figure 3 This is the X-ray diffraction spectrum of comparative sample 1.

[0062] Figure 4 This is the X-ray diffraction spectrum of comparative sample 2.

[0063] Figure 5 This is a SEM photograph of the surface morphology of sample 1 in Example 1 of the present invention.

[0064] Figure 6 This is a SEM photograph of the surface morphology of sample 2 in Example 1 of the present invention.

[0065] Figure 7 This is the SEM photo of the surface morphology of comparison sample 1.

[0066] Figure 8 This is the SEM photo of the surface morphology of comparison sample 2.

[0067] Fig. 9 This is a SEM photograph of the cross-sectional morphology of sample 4 in Example 2 of the present invention.

[0068] Fig.10 This is a SEM photograph of the indentation peeling morphology of sample 5 in Example 4 of the present invention.

[0069] Fig.11 This is a SEM photograph of the indentation peeling morphology of comparative sample 5 in Example 4 of the present invention. DETAILED DESCRIPTION

[0070] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the protection scope of the present invention is not limited thereby. The materials and instruments used in the following embodiments are all commercially available.

[0071] Example 1

[0072] A coated cutting tool of the present invention, specifically sample 1 and sample 2 of the present invention, includes a tool substrate and a multilayer coating covered on the surface of the tool substrate, the multilayer coating includes at least one layer of MTCVD TiCN coating with a columnar crystal structure, and the MTCVD TiCN coating has a (220) crystal plane preferred texture orientation.

[0073] In sample 1 of the present invention:

[0074] The texture coefficient Tc(220) is 6.01, the diffraction angle 2θ of the (220) crystal plane is 60.96°, the grain size of the MTCVD TiCN coating is 0.25 μm, and the thickness of the MTCVD TiCN coating is 12.0 μm.

[0075] A hard base layer is also provided between the MTCVD TiCN coating and the tool substrate. The hard base layer is a TiN layer with a thickness of 0.1 μm.

[0076] In sample 2 of the present invention:

[0077] The texture coefficient Tc(220) is 3.1, the diffraction angle 2θ of the (220) crystal plane is 61.01°, the grain size of the MTCVD TiCN coating is 0.36 μm, and the thickness of the MTCVD TiCN coating is 7.0 μm.

[0078] A hard base layer is also provided between the MTCVD TiCN coating and the tool substrate. The hard base layer is a TiN layer with a thickness of 0.5 μm.

[0079] A method for preparing a coated cutting tool of the present invention comprises the following steps:

[0080] (1) A carbide cutting tool substrate with a blade model of CNMG120408 was selected, and the substrate composition was 6wt% Co, 0.2wt% Ti and Ta cubic carbonitride, and the balance WC. Coating was carried out in a BPX pro 530L CVD coating equipment. Before coating, the substrate was wet blasted to improve the surface cleanliness and smoothness of the substrate, and the blade edge was rounded into an approximate arc structure with a radius of 25μm-45μm.

[0081] (2) First, a TiN coating is deposited on the tool substrate using a mixed gas of 38.5 mol% N2, 1.5 mol% TiCl4 and the remainder H2 at 870°C-930°C and a pressure of 160 mbar to form a hard base layer with a deposition thickness of 0.1 μm-1 μm.

[0082] (3) According to Step A, Step B, Step D and Step E in Table 1, the MTCVD TiCN coatings of Sample 1 and Sample 2 of the present invention and the MTCVD TiCN coatings of Comparative Sample 1 and Comparative Sample 2 were prepared respectively.

[0083] The MTCVD TiCN coating was analyzed by X-ray diffraction using CuKa radiation. The XRD diffraction spectra of the MTCVD TiCN coatings of Sample 1 and Sample 2 of the present invention are as follows: Figure 1 and Figure 2 As shown in Figure 2, the (220) diffraction peak is the highest. The XRD diffraction spectra of the MTCVD TiCN coatings of Comparative Sample 1 and Comparative Sample 2 are shown in Figure 2. Figure 3 and Figure 4 As shown, the (220) diffraction peak is lower than the (311) or (422) diffraction peak. The texture coefficient Tc (hkl) of the MTCVD TiCN coating of the present invention and the texture coefficient Tc (hkl) of the comparative MTCVD TiCN coating are shown in Table 2. The texture coefficient Tc (220) of sample 1 and sample 2 of the present invention is 3.10 at the minimum and 6.01 at the maximum, and the Tc (220) texture accounts for 44.29%-85.86%. Its texture coefficient Tc (220) is higher than the texture coefficient Tc (220) of comparative example 1 and comparative example 2.

[0084] Table 1 MTCVD TiCN coating deposition parameters of the samples of the present invention and the comparative samples

[0085]

[0086] Table 2 Comparison of the texture coefficient Tc (hkl) of the MTCVD TiCN coating of the sample of the present invention and the comparative sample

[0087]

[0088] The surface SEM morphologies of the MTCVD TiCN coatings of Sample 1 and Sample 2 of the present invention are as follows: Figure 5 , Figure 6 The surface SEM morphologies of the MTCVD TiCN coatings of Comparative Sample 1 and Comparative Sample 2 are shown in Figure 2. Figure 7 , Figure 8 The grain size of the MTCVD TiCN coating of sample 1 and sample 2 of the present invention is finer than that of comparative sample 1, and slightly coarser than that of comparative sample 2.

[0089] The diffraction angle 2θ value, thickness, grain size and nanohardness results of the (220) crystal plane of the MTCVD TiCN coating of the present invention's sample 1, sample 2 and comparative sample 1, comparative sample 2 are shown in Table 3. The diffraction angle 2θ of the (220) crystal plane of the MTCVD TiCN coating of the present invention's sample 1 and sample 2 are 60.96° and 61.01°, respectively, and the grain sizes are 0.25μm and 0.36μm, respectively. The grain size is measured by the following method: the sample is a cross-sectional metallographic sample of the coating product, the surface normal of the cross section is perpendicular to the surface normal of the substrate, and the average value of the width of the grain on the straight line parallel to the substrate surface at the middle position of the upper and lower interfaces of the MTCVD TiCN coating on the cross section.

[0090] The nanohardness values ​​of the MTCVD TiCN coatings of Sample 1 and Sample 2 of the present invention are 27.9 GPa and 27.1 GPa respectively. The nanohardness of the coating is detected by nanoindentation method with a maximum load of 30.00 mN, a loading rate of 60.00 mN / min, an unloading rate of 60.00 mN / min, and a dwell time of 10.0 s.

[0091] The grain size of comparative sample 1 is 0.61 μm, TC(220) is 2.11, and the nanohardness is 25.5 GPa. Compared with comparative sample 1, samples 1 and 2 of this embodiment have higher Tc(220) and finer grain sizes of the coatings.

[0092] The diffraction angle 2θ of the (220) crystal plane of comparative sample 2 is 61.07°, TC(220) is 0.44, and the grain size is 0.19 μm. The nanohardness is 20.3 GPa. Compared with comparative sample 2, samples 1 and 2 of this embodiment have the same grain size, high Tc(220), and low diffraction angle 2θ.

[0093] Compared with Comparative Sample 1 and Comparative Sample 2, the coating of this embodiment has high hardness.

[0094] Table 3 Comparison of 2θ, grain size and nanohardness of MTCVD TiCN coatings of the present invention and comparative samples

[0095] sample <![CDATA[2θ 220 (°)]]> Grain size (μm) Nanohardness(GPa) Sample 1 of the present invention 60.96 0.25 27.9 Sample 2 of the present invention 61.01 0.36 27.1 Comparative sample 1 60.99 0.61 25.5 Comparative sample 2 61.07 0.19 20.3

[0096] Example 2

[0097] A coated cutting tool of the present invention, specifically sample 3 and sample 4 of the present invention, includes a tool substrate and a multilayer coating covered on the surface of the tool substrate, the multilayer coating includes at least one layer of MTCVD TiCN coating with a columnar crystal structure, and the MTCVD TiCN coating has a (220) crystal plane preferred texture orientation.

[0098] In sample 3 of the present invention:

[0099] The texture coefficient Tc(220) is 5.54, the diffraction angle 2θ of the (220) crystal plane is 60.89°, the grain size of the MTCVD TiCN coating is 0.20 μm, and the thickness of the MTCVD TiCN coating is 9.1 μm.

[0100] A hard base layer, a MTCVD TiCN coating, an intermediate layer and an α-Al2O3 coating are arranged on the tool substrate in sequence.

[0101] The hard base layer is a TiN layer with a thickness of 0.3 μm.

[0102] The thickness of the α-Al2O3 coating is 5 μm.

[0103] The middle layer includes a HT TiCN layer and a TiCO layer, the outer layer is a TiCO layer, and the total thickness of the middle layer is 0.5 μm.

[0104] In sample 4 of the present invention:

[0105] The texture coefficient Tc(220) is 4.1, the diffraction angle 2θ of the (220) crystal plane is 61.02°, the grain size of the MTCVD TiCN coating is 0.33 μm, and the thickness of the MTCVD TiCN coating is 8.5 μm.

[0106] A hard base layer, a MTCVD TiCN coating, an intermediate layer and an α-Al2O3 coating are arranged on the tool substrate in sequence.

[0107] The hard base layer is a TiN layer with a thickness of 0.2 μm.

[0108] The thickness of the α-Al2O3 coating is 5 μm.

[0109] The middle layer includes a HT TiCN layer and a TiCO layer, the outer layer is a TiCO layer, and the total thickness of the middle layer is 0.5 μm.

[0110] A method for preparing a coated cutting tool of the present invention comprises the following steps:

[0111] (1) A carbide cutting tool substrate with a blade model of CNMG120408 was selected, and the substrate composition was 6wt% Co, 0.2wt% Ti and Ta cubic carbonitride, and the balance WC. Coating was carried out in a BPX pro 530L CVD coating equipment. Before coating, the tool substrate was wet blasted to improve the surface cleanliness and smoothness of the substrate, and the blade edge was rounded into an approximate arc structure with a radius of 25μm-45μm.

[0112] (2) First, a TiN coating with a thickness of 0.1 μm to 1 μm is deposited on the tool substrate using a mixed gas of 38.5 mol% N2, 1.5 mol% TiCl4 and the remainder H2 at 870°C to 930°C and a pressure of 160 mbar.

[0113] (3) According to Step A, Step B, Step D and Step E in Table 1, the MTCVD TiCN coatings of Sample 3 and Sample 4 of the present invention and the MTCVD TiCN coatings of Comparative Sample 3 and Comparative Sample 4 were prepared.

[0114] (4) An intermediate layer is deposited on the MTCVD TiCN coating. The intermediate layer is deposited in two steps. First, a HT TiCN layer is deposited according to Step H in Table 4, and then a TiCO layer is deposited according to Step I. The total thickness of the HT TiCN and TiCO layers is 0.5 μm.

[0115] (5) An Al2O3 coating is deposited on the intermediate layer. The Al2O3 coating is deposited in three steps. First, the TiCO layer is oxidized according to Step J in Table 4, and then an Al2O3 layer is deposited according to Step K and Step L. The thickness of the layer is 5 μm and the Tc(006) is 2.5.

[0116] The cross-sectional SEM morphology of sample 4 of the present invention is as follows: Fig. 9 As shown, starting from the carbide tool substrate, there are TiN layer, MTCVD TiCN layer, middle layer and Al2O3 layer upwards.

[0117] Table 4 Deposition parameters of the intermediate layer and Al2O3 coating of the samples of the present invention and the comparative samples

[0118]

[0119]

[0120] Table 5 Comparison of the texture coefficient Tc (hkl) of the MTCVD TiCN coating of the sample of the present invention and the comparative sample

[0121]

[0122] The texture coefficients Tc(hkl) of the MTCVD TiCN coatings of samples 3 and 4 of the present invention and comparative samples 3 and 4 are shown in Table 5. The TC(220) of samples 3 and 4 of the present invention is higher than that of comparative samples 3 and 4.

[0123] Example 3

[0124] Nanohardness analysis was used to analyze the hardness of the MTCVD TiCN layer and Al2O3 layer of samples 3 and 4 of the present invention and comparative samples 3 and 4 in Example 2. As shown in Table 6, the thickness of the MTCVD TiCN coating of samples 3 and 4 of the present invention is 9.1μm and 8.5μm, respectively, and the nanohardness is 28.2GPa and 27GPa, respectively. The thickness of the Al2O3 layer is about 5μm, and the nanohardness is about 27.0GPa. The thickness of the MTCVD TiCN coating of comparative samples 3 and 4 is 8.3μm and 9.5μm, respectively, and the nanohardness is 25.1GPa and 21.3GPa, respectively. The thickness of the Al2O3 layer is about 5μm, and the nanohardness is about 27Pa.

[0125] Table 6 Comparison of thickness and nanohardness of MTCVD TiCN coatings of Example 2 samples and comparative samples

[0126]

[0127] The wear resistance of the coating product was evaluated by gray iron turning experiment, with the blade flank wear value VB = 0.3 mm as the blade failure judgment standard, and the blade cutting time (blade life) when the blade flank wear value VB = 0.3 mm was used to evaluate the wear resistance of the blade. The longer the blade life, the better the wear resistance. Samples 3 and 4 of the present invention and comparative samples 3 and 4 were tested under different cutting conditions. The results are shown in Table 7 below. The cutting test conditions are as follows:

[0128] Workpiece material: Grey cast iron HT300

[0129] Processing method: dry turning

[0130] Cutting speed: 600m / min, 500m / min

[0131] Cutting depth: 1.0mm

[0132] Feed rate: 0.2mm / r

[0133] Table 7 Comparison of cutting life of coated tools of example samples and comparative samples

[0134]

[0135] The test shows that: in the high-speed processing of gray cast iron HT300, the service life of the coated blade samples 3 and sample 4 of the present invention is significantly improved compared with the comparative samples 3 and sample 4; in the low-speed processing of gray cast iron HT300, the service life of the coated blade samples 3 and sample 4 of the present invention is significantly improved compared with the comparative samples 3 and sample 4.

[0136] Compared with the comparative blade, the service life of the coated blade of the present invention is significantly improved, indicating that the wear resistance of the coated blade of the present invention is better than that of the comparative blade.

[0137] Example 4

[0138] A coated cutting tool of the present invention comprises a tool substrate and a multilayer coating covering the surface of the tool substrate, wherein the multilayer coating comprises at least one layer of MTCVD TiCN coating having a columnar crystal structure, and the MTCVD TiCN coating has a (220) crystal plane preferred texture orientation.

[0139] In sample 5 of the present invention:

[0140] The texture coefficient Tc(220) is 3.76, the diffraction angle 2θ of the (220) crystal plane is 60.79°, the grain size of the MTCVD TiCN coating is 0.14 μm, and the thickness of the MTCVD TiCN coating is 8.0 μm.

[0141] A hard base layer, a MTCVD TiCN coating, an intermediate layer and an α-Al2O3 coating are arranged on the tool substrate in sequence.

[0142] The hard base layer is a TiN layer with a thickness of 0.2 μm.

[0143] The thickness of the α-Al2O3 coating is 5.0 μm.

[0144] The middle layer includes a HT TiCN layer and a TiCO layer arranged from bottom to top, and the total thickness of the middle layer is 0.5 μm.

[0145] A method for preparing the coated cutting tool of this embodiment comprises the following steps:

[0146] (1) A carbide cutting tool substrate with a blade model of CNMG120408 was selected, and the substrate composition was 6wt% Co, 5.5wt% Ti and Ta cubic carbonitride, and the balance WC. Coating was carried out in a BPX pro 530L CVD coating equipment. Before coating, the tool substrate was wet blasted to improve the surface cleanliness and smoothness of the substrate, and the blade edge was rounded into an approximate arc structure with a radius of 25μm-45μm.

[0147] (2) First, a TiN coating with a thickness of 0.1 μm to 1 μm is deposited on the tool substrate using a mixed gas of 38.5 mol% N2, 1.5 mol% TiCl4 and the remainder H2 at 870°C to 930°C and a pressure of 160 mbar.

[0148] (3) According to Step C and Step F in Table 1, the MTCVD TiCN coating of sample 5 of the present invention and the MTCVD TiCN coating of comparative sample 5 were prepared.

[0149] (4) An intermediate layer is deposited on the MTCVD TiCN coating. The intermediate layer is deposited in two steps. First, a HT TiCN layer is deposited according to Step H in Table 4, and then a TiCO layer is deposited according to Step I. The total thickness of the HT TiCN and TiCO layers is 0.5 μm.

[0150] (5) An Al2O3 coating is deposited on the intermediate layer. The Al2O3 coating is deposited in three steps. First, the TiCO layer is oxidized according to Step J in Table 4, and then an Al2O3 layer is deposited according to Step K and Step L. The thickness of the layer is 5 μm and the Tc(006) is 2.5.

[0151] (6) Using a mixed gas of 38.5 mol% N2, 1.5 mol% TiCl4 and the remainder H2, a TiN coating was deposited on Al2O3 as a color layer at 870°C-930°C and a pressure of 160 mbar to obtain sample 5 of the present invention and comparative sample 5.

[0152] The orientation of the MTCVD TiCN coating of the sample 5 of the present invention and the comparative sample 5 is shown in Table 8, and the diffraction angle 2θ value of the (220) crystal plane, the peeling grade, the grain size and the nanohardness results are shown in Table 9. The diffraction angle 2θ of the (220) crystal plane of the sample 5 of the present invention is 60.79, the TC(220) is 3.76, the grain size is 0.14μm, and the nanohardness is 29.1GPa. The diffraction angle 2θ of the (220) crystal plane of the comparative sample 5 is 60.71, the TC(220) is 0.73, the grain size is 0.13μm, and the nanohardness is 22.1GPa. Compared with the comparative sample 5, the sample 5 of the present invention has a high Tc(220) and a high diffraction angle 2θ.

[0153] The indentation peeling method was used to analyze the anti-stripping performance of the coating. The higher the indentation peeling grade, the lower the anti-stripping performance. The indentation peeling morphologies of sample 5 of the present invention and comparative sample 5 are as follows: Fig.10 and Fig.11 As shown, the comparison of the indentation peeling results shows that the sample 5 of the present invention has good anti-peeling performance.

[0154] Table 8 Comparison of texture coefficient Tc (hkl) of MTCVD TiCN coating of the present invention sample and comparative sample

[0155]

[0156] Table 9 Performance comparison of MTCVD TiCN coatings of the present invention samples and comparative samples

[0157]

[0158]

[0159] Example 5

[0160] The wear resistance of the sample 5 of the present invention and the comparative sample 5 under different cutting conditions was evaluated by a 45# steel turning experiment. The blade flank wear value VB=0.3 mm was used as the blade failure judgment standard. The blade cutting time (blade life) when the blade flank wear value VB=0.3 mm was used to evaluate the wear resistance of the blade. The longer the blade life, the better the wear resistance. The cutting test results are shown in Table 10 below. The cutting test conditions are as follows:

[0161] Workpiece material: 45#

[0162] Processing method: dry turning

[0163] Cutting speed: 350m / min

[0164] Cutting depth: 1.0mm

[0165] Feed rate: 0.2mm / r

[0166] Table 10 Comparison of cutting life of coated tools of the present invention samples and comparative samples

[0167] sample Blade life (min) Sample 5 of the present invention 35 Comparative sample 5 28

[0168] Tests show that in the turning process of 45# steel, the coated blade of the present invention has a longer blade life and better wear resistance than the comparative blade.

[0169] Example 6

[0170] The impact resistance of the coating product was evaluated by turning impact test of 45# steel four-groove round bar, with tip chipping as the blade failure judgment standard, and the number of blade impacts as the blade impact resistance evaluation, the more impacts, the better the impact resistance. The test results are shown in Table 11 below, and the cutting test conditions are as follows:

[0171] Workpiece material: 45# steel four-slot round bar

[0172] Processing method: dry turning

[0173] Cutting speed: 220r / min

[0174] Cutting depth: 1.0mm

[0175] Feed rate: 0.2mm / r

[0176] Table 11 Comparison of coating tool impact test of the samples of the present invention and the comparative samples

[0177] sample Number of impacts Sample 5 of the present invention 4400 Comparative sample 5 1085

[0178] Tests show that the coated blade of the present invention has significantly better impact resistance than the comparative blade.

[0179] In summary, the MTCVD TiCN coating of the coated cutting tool of the present invention is controlled by controlling the organization structure such as orientation, grain size, composition, etc., the texture coefficient Tc(220)≥3, the diffraction angle 2θ of the (220) crystal plane is between 60.75° and 61.05°, and the grain size of the MTCVDTiCN coating is between 0.1μm and 0.4μm. Compared with the prior art, the hardness of the coating is significantly improved, the wear resistance of the coated tool is improved, the impact resistance and anti-stripping performance of the coated blade are improved, and the stability is improved.

[0180] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as above in the preferred embodiment, it is not used to limit the present invention. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the methods and technical contents disclosed above without departing from the spirit and technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Therefore, any simple modification, equivalent replacement, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention, still fall within the scope of protection of the technical solution of the present invention.

Claims

1. A coated cutting tool, characterized in that: It includes a tool substrate and a multilayer coating covered on the surface of the tool substrate, wherein the multilayer coating includes at least one layer of MTCVD TiCN coating with a columnar crystal structure, the MTCVD TiCN coating has a (220) crystal plane preferential texture orientation, a texture coefficient Tc(220)≥3, and a diffraction angle 2θ of the (220) crystal plane in the range of 60.75° to 61.05°; the grain size of the MTCVD TiCN coating is 0.1μm to 0.4μm.

2. The coated cutting tool according to claim 1, characterized in that The Tc(220) of the MTCVD TiCN coating is ≥4.

3. The coated cutting tool according to claim 2, characterized in that The Tc(220) of the MTCVD TiCN coating is ≥5.

4. The coated cutting tool according to claim 1, characterized in that In an X-ray diffraction analysis using CuKa radiation, the diffraction angle 2θ of the (220) crystal plane of the MTCVD TiCN coating is between 60.85° and 60.95°.

5. The coated cutting tool according to claim 1, characterized in that The grain size of the MTCVD TiCN coating is 0.15 μm to 0.3 μm.

6. The coated cutting tool according to claim 1, characterized in that The thickness of the MTCVD TiCN coating is 5 μm to 20 μm.

7. The coated cutting tool according to claim 6, characterized in that The thickness of the MTCVD TiCN coating is 7 μm to 15 μm.

8. The coated cutting tool according to any one of claims 1 to 7, characterized in that: A hard base layer is further provided between the MTCVD TiCN coating and the tool substrate. The hard base layer comprises at least one of a TiN layer, a TiCN layer and a TiC layer. The thickness of the hard base layer is 0.1 μm to 1.0 μm.

9. The coated cutting tool according to claim 8, characterized in that The surface of the MTCVD TiCN coating is provided with an Al2O3 coating, and the thickness of the Al2O3 coating is 2 μm to 15 μm.

10. The coated cutting tool according to claim 9, characterized in that The thickness of the Al2O3 coating is 3 μm to 10 μm; the Al2O3 coating is an α-Al2O3 coating or a k-Al2O3 coating.

11. The coated cutting tool according to claim 10, characterized in that The thickness of the Al2O3 coating is 4 μm to 7 μm.

12. The coated cutting tool according to any one of claims 9 to 11, characterized in that: An intermediate layer is provided between the MTCVD TiCN coating and the Al2O3 coating, and the intermediate layer is composed of two or more layers of a TiN layer, a TiCN layer, a TiCNO layer, a TiAlCNO layer and a TiCO layer. The outermost layer of the intermediate layer is one of a TiCNO layer, a TiAlCNO layer and a TiCO layer, and the thickness of the intermediate layer is 0.3μm to 1.0μm.

13. The coated cutting tool according to claim 12, characterized in that A color layer is provided on the surface of the Al2O3 coating, and the color layer includes a combination of one or more layers of a TiN layer, a ZrN layer, a TiC layer and a TiB layer, and the thickness of the color layer is 0.2 μm to 2.0 μm.

14. A method for preparing a coated cutting tool according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Prepare the tool base; (2) A TiCN coating is deposited by an MTCVD process to obtain an MTCVD TiCN coating, wherein the process conditions include: a deposition temperature of 870°C to 950°C, a pressure of 40 mbar to 100 mbar, TiCl4-CH3CN-HCl-N2-H2 as a deposition atmosphere system, and a reaction gas comprising 10.0 mol% to 50.0 mol% N2, 1.0 mol% to 4.0 mol% TiCl4, 0.2 mol% to 1 mol% CH3CN, 0 to 5 mol% HCl, and the remainder being H2 gas, wherein the molar ratio of TiCl4 to CH3CN is 4 to 7:

1.

15. The method for preparing a coated cutting tool according to claim 14, characterized in that: The step of depositing a hard base layer is also included between step (1) and step (2): a hard base layer is deposited on the tool substrate using a CVD process, and then a MTCVD TiCN coating is deposited on the hard base layer; the hard base layer includes at least one of a TiN layer, a TiCN layer and a TiC layer, and the thickness of the hard base layer is 0.1 μm to 1.0 μm.

16. The method for preparing a coated cutting tool according to claim 15, characterized in that: The step (2) also includes the step of depositing an intermediate layer: depositing the intermediate layer on the MTCVD TiCN coating using a CVD process; the intermediate layer includes a combination of one or more layers of a TiN layer, a TiCN layer, a TiCNO layer, a TiAlCNO layer and a TiCO layer, and the thickness of the intermediate layer is 0.3 μm to 1.0 μm.

17. The method for preparing a coated cutting tool according to claim 16, characterized in that: After depositing the intermediate layer, the method further includes depositing an Al2O3 coating: depositing the Al2O3 coating on the intermediate layer using a CVD process; the thickness of the Al2O3 coating is 2 μm to 15 μm.

18. The method for preparing a coated cutting tool according to claim 17, characterized in that: After depositing the Al2O3 coating, the step of depositing a color layer is also included: a color layer is deposited on the Al2O3 coating using a CVD process; the color layer includes a combination of one or more layers of a TiN layer, a ZrN layer, a TiC layer and a TiB layer, and the thickness of the color layer is 0.2μm to 2.0μm.

Citation Information

Patent Citations

  • Coated cutting tool and method for producing the same

    CN101138900B

  • Coated cutting tool and method of manufacturing the same

    CN104053815A

  • Coated Cutting Tools

    CN105308210B